Method for rapidly identifying authenticity of gambiered canton silk product by utilizing Py-GC / MS
Through Py-GC/MS technology, the black coating substances of yarn products are thermally cracked and GC/MS analysis are analyzed, and their characteristic components are identified, which solves the problem of yarn identification, and achieves rapid and accurate authenticity identification, improving the quality and futility identification. The objectivity and efficiency of identification are achieved.
Patent Information
- Application Number
- CN202411251096.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-10
AI Technical Summary
It is difficult to accurately and efficiently identify the authenticity of yarn silk products in the existing technology, especially imitations of yarn silk products, which are easy to get away with, resulting in a large number of counterfeit products on the market, affecting consumers and industries.
Using thermal cracking-gas chromatography/mass spectrometry combined technology (Py-GC/MS), the black coating substance of the yarn product is thermally cracked at a high temperature of 500-600℃ to generate a gasified cracking product. GC/MS analysis was performed using gas chromatography/mass spectrometer, and the spectra were structured to identify the spectra in combination with the NIST17 library to determine whether the sample contained characteristic components such as catechol, indole and 3-methylcatechol.
It realizes the authenticity of yarn silk products conveniently, efficiently and objectively, accurately distinguishes between genuine and imitation products, avoids the subjectivity of visual and hand identification, and improves the accuracy and reliability of identification.
Smart Images

Figure CN119291056A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of analysis and detection, and in particular to a method for quickly identifying the authenticity of a ramie silk product by utilizing Py-GC / MS. Background Art
[0002] The traditional processing technology of ramie silk is to dye silk with yam pigment extract, then expose it to the sun, repeat more than 20 times, and finally apply river mud to the silk surface, react for 30-60 minutes, wash off the excess river mud, and dry it in the sun. The mud-coated side of ramie silk is a glossy black coating, and the reverse side is brown. It has a special style and is comfortable to use, and is deeply loved by consumers. Due to its special preparation method, the black coating on the front side contains specific ingredients.
[0003] Since the production process of ramie silk is complicated and purely handmade, its processing is limited to Guangdong and Guangxi, and the annual output of finished products is limited, which makes the market price of ramie silk high. As a result, various imitation ramie silk products have appeared on the market. The most common one is to mix chemical synthetic dyes with paste to make color paste, which is scraped and applied on the surface of the fabric to form a counterfeit product that looks similar to ramie silk. It has a large output, low cost, and realistic appearance and feel, which has caused serious harm to consumers and the ramie silk industry. Therefore, accurate and efficient identification methods for ramie silk products are very important.
[0004] At present, although a chemical color development method for identifying cocoon and silk products has been developed, such as the literature - Research on the identification method of ramie silk based on the color development principle of phenolic reaction. Silk, 2024, 61(7): 84-90; it is easy to be fooled by fake ramie silk products soaked in ramie dye (ramie pigment extract). In the market, the identification of ramie silk mainly relies on experienced manufacturers and retailers to distinguish the authenticity based on the visual and tactile effects of the products, which is difficult for consumers to master.
[0005] Pyrolysis-gas chromatography / mass spectrometry (Py-GC / MS) is an analytical method that combines pyrolysis technology with gas chromatography-mass spectrometry. Under high temperature conditions, the sample is decomposed into small volatile molecules, and the characteristics of the pyrolysis products are analyzed by gas chromatography-mass spectrometry to identify the sample. Py-GC / MS technology has the advantages of accurate analysis results, fast speed, high sensitivity, small sample usage and no need for pretreatment.
[0006] There is currently no method for using Py-GC / MS to identify yarn and silk. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a method for quickly identifying the authenticity of ramie silk products by using Py-GC / MS.
[0008] In order to solve the above technical problems, the present invention provides a method for quickly identifying the authenticity of ramie silk products by using Py-GC / MS, comprising the following steps:
[0009] 1) Sample pretreatment:
[0010] Take the genuine and fake ramie silk products as the samples to be tested, and scrape the coating material (sediment) on the black surface of the samples to be tested as the components to be tested;
[0011] 2) Py-GC / MS test:
[0012] A pyrolysis gas chromatography / mass spectrometer equipped with the NIST17 spectral library was selected;
[0013] The component to be tested is placed in a thermal cracker (a sample cup of the thermal cracker); the thermal cracking conditions are as follows: the thermal cracking temperature is 500-600°C, the cracking time is 18±2s, and the interface temperature is 300±20°C; after the component to be tested is thermally cracked, a gasified cracking product is formed;
[0014] Using a gas chromatograph / mass spectrometer to perform GC / MS determination on the pyrolysis products of the component to be measured (i.e., performing qualitative and quantitative analysis on the chemical components of the pyrolysis products);
[0015] The NIST17 spectral library provided by the gas chromatograph / mass spectrometer was used to perform structural identification on the GC / MS chromatographic peaks;
[0016] 3) Result determination:
[0017] When the NIST17 spectral library shows that the thermal decomposition products of the sample to be tested include catechol (C6H6O2), indole (C8H7N) and 3-methylcatechol (C7H8O2) according to the Py-GC / MS spectrum of the component to be tested, the sample to be tested is determined to be a ramie silk product;
[0018] Otherwise, the sample to be tested is determined to be an imitation of ramie silk.
[0019] As an improvement of the method for quickly identifying the authenticity of ramie silk products using Py-GC / MS of the present invention:
[0020] The GC / MS determination of step 2):
[0021] The gas chromatographic column used was a medium polarity column DB-5MS (30m×250μm×0.25μm, with a phenyl arylene polymer as the stationary phase); the injection port temperature was 300°C; the split ratio was 20:1; helium (purity ≥99.999%), the carrier gas flow rate was 1mL / min (constant flow mode); the column temperature program was an initial temperature of 40°C, maintained for 5min, and then heated to 300°C at 10°C / min and maintained for 5min;
[0022] Mass spectrometry conditions: EI source; ion source temperature: 230°C; quadrupole temperature: 150°C; mass spectrometry interface temperature: 300°C; electron impact energy: 70 eV; mass scanning range: m / z 15-450.
[0023] As a further improvement of the method for rapidly identifying the authenticity of ramie silk products using Py-GC / MS of the present invention, in step 3):
[0024] The sample to be tested is determined to be a ramie silk product when the peak area of the chromatographic peak with a retention time of 5 to 35 minutes is calculated and the following conditions are met at the same time: the peak area percentage corresponding to catechol is 3.0% to 6.0%, the peak area percentage corresponding to indole is 1.0% to 2.5%, and the peak area percentage corresponding to 3-methylcatechol is 0.2% to 1.0%;
[0025] Otherwise, the sample to be tested is determined to be an imitation of ramie silk.
[0026] As a further improvement of the method for rapidly identifying the authenticity of ramie silk products using Py-GC / MS of the present invention, a 7890B-5977A gas chromatograph / mass spectrometer (Agilent, USA) with a built-in PY-3030D microfurnace pyrolyzer (Frontier, Japan) was used.
[0027] As a further improvement of the method for quickly identifying the authenticity of ramie silk products using Py-GC / MS of the present invention, in step 2), the amount of the component to be tested is 1 mg. That is, 1 mg of the component to be tested is placed in the thermal cracker.
[0028] As a further improvement of the method for rapidly identifying the authenticity of ramie silk products using Py-GC / MS of the present invention:
[0029] The sample to be tested is directly tested, and the result obtained is named as the result of the sample to be tested before washing;
[0030] The sample to be tested is first rinsed in pure water for 5±1 minutes, and then naturally air-dried to constant weight; then the washed sample to be tested is tested, and the result obtained is named the result of the washed sample to be tested;
[0031] If any of the peak area percentages of catechol, indole and 3-methylcatechol in the test sample after washing is significantly lower than that of the test sample before washing (lower than 20%), the test sample is determined to be a ramie silk imitation product;
[0032] Otherwise, the sample to be tested is determined to be a ramie silk product.
[0033] The principle of the present invention is as follows: the black coating material on the surface of the sample to be tested is scraped off, and Py-GC / MS analysis is performed under certain conditions, and the qualitative identification of the true and false ramie silk products is performed according to the Py-GC / MS spectrum characteristics. Since the ramie silk products use pure natural ramie pigment and river mud as raw materials, the surface of the product contains the effective components of ramie pigment and river mud (ramie tannin and river mud humus). The coating material on the surface of the sample is thermally cracked into small molecular components under certain conditions by a Py-GC / MS instrument, and then GC / MS analysis is performed. According to whether the GC / MS spectrum of the sample contains characteristic cracking products of ramie tannin and river mud humus (catechol, indole, 3-methylcatechol), and whether the relative content of the characteristic products meets the judgment standard, it is judged whether the sample to be tested is a true ramie silk product.
[0034] In the present invention, the thermal cracking temperature is one of the most critical factors. When the temperature is too low, the characteristic cracking products are difficult to produce, while when the temperature is too high, the characteristic products are over-cracked, the content is low, and the signal is weak. The present invention has been repeatedly verified that the thermal cracking temperature is optimal at 500-600°C.
[0035] The method of the present invention can be used to conveniently, efficiently and objectively identify the authenticity of ramie silk. According to the chemical composition characteristics of the surface coating of ramie silk, the present invention analyzes the sediment on the surface of the fabric by pyrolysis-gas chromatography / mass spectrometry (Py-GC / MS), clarifies the characteristics of the pyrolysis products of the surface components of ramie silk, and proposes a basis for using this method to identify the authenticity of ramie silk. The research results show that the pyrolysis products of ramie silk products are catechol, indole and benzene 4-methylcatechol; finally, the method is verified using representative ramie silk samples, and it is clear that the method is accurate and feasible. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings.
[0037] Figure 1 This is the Py-GC / MS graph of sample No. 1;
[0038] Figure 2 This is the Py-GC / MS graph of sample No. 2;
[0039] Figure 3 This is the Py-GC / MS graph of sample #3.
[0040] Figure 4 This is the Py-GC / MS graph of sample #4.
[0041] Samples 1#, 2# and 3# were identified as genuine ramie silk products by the inheritors of the national intangible cultural heritage of ramie silk dyeing and finishing technology. Sample 1# came from Hangzhou Tianyi Biomaterial Co., Ltd., sample 2# came from Foshan Shunde Langzhuji Silk Co., Ltd., and sample 3# came from Foshan Jianshengxuan Textile Co., Ltd.; sample 4# was a ramie silk imitation (a product dyed and finished with synthetic dyes) from Zhejiang Misai Silk Co., Ltd. All of the above are commercial products. DETAILED DESCRIPTION
[0042] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:
[0043] Example 1: A method for quickly identifying the authenticity of ramie silk products using Py-GC / MS, comprising the following steps: 1. Sample pretreatment:
[0044] Use a blade to gently scrape the coating material on the black surface of the sample to be tested (the black coating is formed by the reaction and deposition of yam pigment and river mud), take 1 mg of the scraped sediment and put it in a sample cup, place it in a thermal cracker, and perform Py-GC / MS analysis.
[0045] 2. Py-GC / MS test
[0046] 7890B-5977A gas chromatograph / mass spectrometer (Agilent, USA), which is equipped with a PY-3030D microfurnace pyrolyzer (Frontier, Japan).
[0047] Thermal cracking conditions: thermal cracking temperature is 500-600℃, cracking time is 18s, and interface temperature is 300℃.
[0048] Note: Interface temperature is the temperature of the interface between the pyrolyzer component and the gas chromatograph component.
[0049] After the above-mentioned thermal cracking, the sediment forms gasified cracking products;
[0050] GC / MS conditions: Use gas chromatography / mass spectrometry to automatically analyze the chemical composition of the gasified pyrolysis products of the sample:
[0051] The gas chromatographic column selected was a medium-polarity column DB-5MS (30m×250μm×0.25μm, with phenylarylene polymer as the stationary phase); the injection port temperature was 300°C; the split ratio was 20:1; helium (purity ≥99.999%), and the carrier gas flow rate was 1mL / min (constant flow mode); the column temperature program was an initial temperature of 40°C, maintained for 5min, and then heated to 300°C at 10°C / min and maintained for 5min.
[0052] Mass spectrometry conditions: EI source; ion source temperature: 230°C; quadrupole temperature: 150°C; mass spectrometry interface temperature: 300°C; electron impact energy: 70 eV; mass scanning range: m / z 15-450.
[0053] The structures of the GC / MS chromatographic peaks were identified using the NIST17 spectral library provided by the gas chromatograph / mass spectrometer.
[0054] 3. Result determination: If the thermal decomposition products of the sample given by the NIST17 spectral library according to the Py-GC / MS spectrum of the sample to be tested include catechol (molecular formula C6H6O2), indole (molecular formula C8H7N) and 3-methylcatechol (molecular formula C7H8O2) at the same time, and the peak area percentage corresponding to catechol is 3.0-6.0%, the peak area percentage corresponding to indole is 1.0-2.5%, and the peak area percentage corresponding to 3-methylcatechol is 0.2-1.0%, then the sample to be tested is determined to be a ramie silk product; otherwise, the sample to be tested is determined to be an imitation ramie silk product.
[0055] Experiment 1-1: Sample 1#, which was previously confirmed to be ramie silk, was tested according to the method described in Example 1, and the thermal cracking temperature was set to 550°C.
[0056] The Py-GC / MS graph of sample 1# and the component information corresponding to the chromatographic peaks in the graph are shown as follows: Figure 1 And as shown in Table 1.
[0057] Table 1. Composition information of sample 1# (given by NIST17 spectral library)
[0058]
[0059]
[0060] The peak area percentage of catechol in sample No. 1 is 4.49%, the peak area percentage of indole is 1.67%, and the peak area percentage of 3-methylcatechol is 0.41%; it meets the judgment rule of the composition characteristics of the pyrolysis product of the ramie silk coating set by the present invention---"the peak area percentage corresponding to catechol is 3.0%~6.0%, the peak area percentage corresponding to indole is 1.0%~2.5%, and the peak area percentage corresponding to 3-methylcatechol is 0.2%~1.0%"; therefore, it is judged that sample No. 1 is ramie silk, which is consistent with the facts.
[0061] Experiment 1-2: Change the thermal cracking temperature in Experiment 1-1 from 550°C to 500°C, and the rest is the same as Experiment 1-1.
[0062] The final results showed that the peak area percentage of catechol, indole and 3-methylcatechol in sample No. 1 was 3.52%, 1.29% and 0.28%, respectively. This was consistent with the determination rules for the composition characteristics of the pyrolysis products of ramie silk coatings. Therefore, sample No. 1 was determined to be ramie silk, which was consistent with the facts.
[0063] Experiment 1-3: Change the thermal cracking temperature in Experiment 1-1 from 550°C to 600°C, and the rest is the same as Experiment 1-1.
[0064] The final results showed that the peak area percentage of catechol, indole and 3-methylcatechol in sample No. 1 was 4.01%, 1.55% and 0.33% respectively; the results also met the determination rules of the composition characteristics of the cracking products of ramie silk coating, so sample No. 1 was determined to be ramie silk, which was consistent with the facts.
[0065] Experiment 2: Sample No. 2, which was previously confirmed to be ramie silk, was tested according to the method described in Example 1, and the thermal cracking temperature was set to 500°C.
[0066] The Py-GC / MS graph of sample 2# and the component information corresponding to the chromatographic peaks in the graph are shown as follows: Figure 2 And as shown in Table 2.
[0067] Table 2 Composition information of sample 2# (given by NIST17 spectral library)
[0068]
[0069]
[0070] The peak area percentage of catechol in sample No. 2 is 4.58%, the peak area percentage of indole is 1.62%, and the peak area percentage of 3-methylcatechol is 0.41%, which meets the judgment rules for the composition characteristics of the pyrolysis products of the ramie silk coating set by the present invention; therefore, it is judged that sample No. 2 is ramie silk, which is consistent with the facts.
[0071] Experiment 3: Sample No. 3, which was previously confirmed to be ramie silk, was tested according to the method described in Example 1, and the thermal cracking temperature was set to 600°C.
[0072] The Py-GC / MS graph of sample 3# and the component information corresponding to the chromatographic peaks in the graph are shown as follows: Figure 3 And as shown in Table 3.
[0073] Table 3 Composition information of sample 3# (given by NIST17 spectral library)
[0074]
[0075]
[0076] The peak area percentage of catechol in sample No. 3 is 4.51%, the peak area percentage of indole is 1.65%, and the peak area percentage of 3-methylcatechol is 0.45%, which meets the judgment rules for the composition characteristics of the pyrolysis products of the ramie silk coating set by the present invention; therefore, it is judged that sample No. 3 is ramie silk, which is consistent with the facts.
[0077] Experiment 4: Sample No. 4, which was previously confirmed to be an imitation of ramie silk, was tested according to the method described in Example 1, and the thermal cracking temperature was set to 550°C.
[0078] The imitation ramie silk is made of a color paste made by mixing synthetic dyes and paste, and is formed by scraping and coating it on the silk blank.
[0079] The Py-GC / MS graph of sample 4# and the component information corresponding to the chromatographic peaks in the graph are as follows: Figure 4 and as described in Table 4.
[0080] Table 4 Composition information of sample 4# (given by NIST17 spectral library)
[0081]
[0082]
[0083] No "catechol, indole, and 3-methylcatechol" were detected, so sample No. 4 was determined to be an imitation of ramie silk, which is consistent with the facts.
[0084] Moreover, when the thermal cracking temperature was changed to 500℃ or 600℃, no "catechol, indole, and 3-methylcatechol" could be detected in sample No. 4.
[0085] In experiment 5, the preparation method of sample No. 5 is as follows: soak the imitation of No. 4 ramie silk in 2 g / L ramie dye solution for 5 minutes, and then dry it at 60°C to constant weight; repeat the above soaking and drying once more.
[0086] Sample #5 was tested according to Experiments 1-1 to 1-3 (i.e., the thermal cracking temperatures were 500°C, 550°C, or 600°C, respectively). The peak area percentages of the obtained catechol, indole, and 3-methylcatechol were 0.2-0.4%, 0%, and 0.05-0.08%, respectively.
[0087] None of them meet the judgment rules for the composition characteristics of the pyrolysis products of the ramie silk coating set by the present invention, so sample 5# is judged to be an imitation of ramie silk, which is consistent with the facts.
[0088] Comparative experiment 1,
[0089] The thermal cracking temperature of Example 1 was changed to 430°C, that is, the thermal cracking temperature was significantly lower than the required range of the present invention; the rest was the same as Example 1. The No. 1 ramie silk product, No. 2 ramie silk product, No. 3 ramie silk product, No. 4 ramie silk imitation and No. 5 ramie silk imitation (the No. 4 ramie silk imitation was dipped in yam dye solution) were tested according to the conditions of comparative experiment 1, and the peak area percentages / % of "catechol, indole, 3-methylcatechol" are shown in Table 5 below.
[0090] Table 5
[0091]
[0092] Comparative Experiment 2: The thermal cracking temperature of Example 1 was changed to 680°C, that is, the thermal cracking temperature was significantly higher than the required range of the present invention; the rest was the same as Example 1. The No. 1 ramie silk product, No. 2 ramie silk product, No. 3 ramie silk product, No. 4 ramie silk imitation product, and No. 5 ramie silk imitation product were tested according to the conditions of Comparative Experiment 2, and the peak area percentages / % of "catechol, indole, and 3-methylcatechol" are shown in Table 6 below.
[0093] Table 6
[0094]
[0095] In summary, it was found that: when the thermal cracking temperature was low, characteristic cracking products of corresponding types and contents could not be obtained, thus leading to erroneous conclusions; when the thermal cracking temperature was too high, the content of characteristic cracking products was low and the signal was weak, thus leading to erroneous conclusions.
[0096] Comparative Experiment 3: Change the heating rate of 10°C / min in Example 1 to 20°C / min; the rest is the same as Example 1. The No. 1 ramie silk product, No. 2 ramie silk product, No. 3 ramie silk product, No. 4 ramie silk imitation product, and No. 5 ramie silk imitation product were tested according to the conditions of Comparative Experiment 3, and the peak area percentages / % of "catechol, indole, and 3-methylcatechol" are shown in Table 7 below.
[0097] Table 7
[0098]
[0099] In summary, it was found that: if the heating rate of the chromatographic column in GC / MS conditions was too fast, it would affect the content ratio of the characteristic pyrolysis products, thus leading to erroneous conclusions; the possible reason may be: the heating rate of the chromatographic column was too fast, resulting in poor separation of the chromatographic peaks, and some characteristic pyrolysis products would be combined with adjacent chromatograms that were close to each other, resulting in a significant increase in the proportion of their chromatographic peak area, causing misjudgment of the results.
[0100] Comparative experiment 4
[0101] Rinse the No. 1, No. 2, and No. 3 ramie silk products in pure water for 5 minutes, and then air dry them to constant weight. Then, test the washed products according to Experiment 1-1, Experiment 2, and Experiment 3 respectively;
[0102] The peak area percentages of catechol, indole, and 3-methylcatechol in the pyrolysis products of sample No. 1 after water washing were not significantly different from those in Table 1.
[0103] The peak area percentages of catechol, indole, and 3-methylcatechol in the pyrolysis products of sample No. 2 after water washing were not significantly different from those in Table 2.
[0104] The peak area percentages of catechol, indole, and 3-methylcatechol in the pyrolysis products of sample No. 3 after water washing were not significantly different from those in Table 1.
[0105] The imitation of camellia silk No. 5 (sample No. 4 was soaked in camellia dye solution and then dried) was rinsed in pure water for 5 minutes and then naturally air-dried to constant weight. The washed sample No. 5 was then tested according to Experiment 1-1, Experiment 2, and Experiment 3, and catechol, indole, and 3-methylcatechol in the washed imitation of camellia silk No. 5 could not be detected.
[0106] The reason is: in the imitation No. 5 ramie silk, the ramie dye solution only adheres to the surface of the fabric. Therefore, during the washing process, the ramie pigment dissolves in the water and is easily removed.
[0107] Therefore, the water-washing pretreatment method can better distinguish the imitation ramie silk formed by the ramie dyeing liquid treatment.
[0108] Note: Since catechol and 3-methylcatechol are both water-soluble components, even if the imitation ramie silk products are soaked in a solution of the above two components and then dried to obtain counterfeit ramie silk products, after the initial washing of such counterfeit ramie silk products, catechol and 3-methylcatechol are also very easily soluble in water, resulting in the contents of catechol and 3-methylcatechol in the samples after washing being greatly reduced relative to the contents of catechol and 3-methylcatechol in the samples before washing, thereby effectively distinguishing such counterfeit ramie silk products.
[0109] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.
Claims
1. A method for rapidly identifying the authenticity of ramie silk products using Py-GC / MS, characterized in that The following steps are involved: 1) Sample pretreatment: Take the genuine and fake ramie silk products as the samples to be tested, and scrape the coating material on the black surface of the samples to be tested as the components to be tested; 2) Py-GC / MS test: A pyrolysis gas chromatography / mass spectrometer equipped with the NIST17 spectral library was selected; The components to be tested are placed in a thermal cracker; the thermal cracking conditions are as follows: the thermal cracking temperature is 500-600°C, the cracking time is 18±2s, and the interface temperature is 300±20°C; after the components to be tested are thermally cracked, gasified cracking products are formed; The pyrolysis products of the components to be tested are measured by GC / MS using a gas chromatograph / mass spectrometer; The NIST17 spectral library provided by the gas chromatograph / mass spectrometer was used to perform structural identification on the GC / MS chromatographic peaks; 3) Result determination: When the NIST17 spectral library shows that the thermal decomposition products of the sample to be tested include catechol, indole and 3-methylcatechol according to the Py-GC / MS spectrum of the component to be tested, the sample to be tested is determined to be a ramie silk product; Otherwise, the sample to be tested is determined to be an imitation of ramie silk.
2. The method for rapidly identifying the authenticity of ramie silk products by using Py-GC / MS according to claim 1, characterized in that: GC / MS determination of step 2): The gas chromatographic column used was a medium polarity column DB-5MS; the injection port temperature was 300°C; the split ratio was 20:1; helium gas, the carrier gas flow rate was 1 mL / min; the column temperature program was an initial temperature of 40°C, maintained for 5 min, and then heated to 300°C at 10°C / min, and maintained for 5 min; Mass spectrometry conditions: EI source; ion source temperature: 230°C; quadrupole temperature: 150°C; mass spectrometry interface temperature: 300°C; electron impact energy: 70 eV; mass scanning range: m / z 15-450.
3. The method for rapidly identifying the authenticity of ramie silk products using Py-GC / MS according to claim 2, characterized in that In the step 3): The sample to be tested is determined to be a ramie silk product when the peak area of the chromatographic peak with a retention time of 5 to 35 minutes is calculated and the following conditions are met at the same time: the peak area percentage corresponding to catechol is 3.0% to 6.0%, the peak area percentage corresponding to indole is 1.0% to 2.5%, and the peak area percentage corresponding to 3-methylcatechol is 0.2% to 1.0%; Otherwise, the sample to be tested is determined to be an imitation of ramie silk.
4. The method for rapidly identifying the authenticity of ramie silk products by using Py-GC / MS according to any one of claims 1 to 3, characterized in that: A 7890B-5977A gas chromatograph / mass spectrometer was selected, which has a built-in PY-3030D microfurnace pyrolyzer.
5. The method for rapidly identifying the authenticity of ramie silk products by using Py-GC / MS according to any one of claims 1 to 4, characterized in that: In the step 2), the amount of the component to be tested is 1 mg.
6. The method for quickly identifying the authenticity of ramie silk products by using Py-GC / MS according to any one of claims 1 to 5, characterized in that: The sample to be tested is directly tested, and the result obtained is named as the result of the sample to be tested before washing; The sample to be tested is first rinsed in pure water for 5±1 minutes, and then naturally air-dried to constant weight; then the washed sample to be tested is tested, and the result obtained is named the result of the washed sample to be tested; If any of the peak area percentages of catechol, indole and 3-methylcatechol in the test sample after washing is significantly lower than that of the test sample before washing, the test sample is determined to be a ramie silk imitation product; Otherwise, the sample to be tested is determined to be a ramie silk product.